Islamic Reform and Colonial Discourse on Modernity in India - Abraham, Jose. author. aut Link
XV, 243 p.
Keywords: In Kerala, Vakkom Moulavi motivated Muslims to embrace modernity, especially modern education, in order to reap maximum benefit. In this process, he initiated numerous religious reforms. However, he held fairly ambivalent attitudes towards individualism, materialism and secularization, defending Islam against the attacks of Christian missionaries.